1993
DOI: 10.1002/pi.4990300403
|View full text |Cite
|
Sign up to set email alerts
|

Water vapour permeability, diffusion and solubility in latex films

Abstract: Water vapour diffusion D, solubility S and permeability P coefficients have been determined for films obtained from carboxylated styrene-butadiene (SB) copolymer latexes. The experimental method is water vapour sorption performed in the range 30-60°C. Using the small angle neutron scattering (SANS) method and a selective labelling with D,O vapour, it has been shown that water molecules mainly diffuse in the films through the particle-particle interfaces, which consist of a polar carboxyl-rich copolymer. It has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

1993
1993
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 11 publications
1
22
1
Order By: Relevance
“…f Particle diameters according to pictures from transmission electron microscopy. 8 Fraction of crosslinked polymer in the core.…”
Section: Methodsmentioning
confidence: 99%
“…f Particle diameters according to pictures from transmission electron microscopy. 8 Fraction of crosslinked polymer in the core.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, L 1 , L 2 , and L 3 , are calculated with the aid of Eqs. (5). If the relative refractive index, m, is known, the polarizability α can be calculated with the aid of Eq.…”
Section: Immersion Patterns: Rayleigh-lorentz Modelmentioning
confidence: 99%
“…The drying temperature has a major effect on film properties such as permeability [1][2][3][4][5] and redispersability [6,7]. In addition to the drying temperature, the relative humidity and the drying time also affect film properties.…”
Section: Introductionmentioning
confidence: 99%
“…Mantanis (1994) mentioned activation energies in the range of 32.2 to 50.2 kJ mol )1 for diffusion in uncoated wood. Richard et al (1993) reported activation energies of 35.2 kJ mol )1 for diffusion of water vapour into carboxylated styrenebutadiene copolymer latexes.…”
Section: Influence Of Temperature On Moisture Diffusionmentioning
confidence: 99%